The Effect Of Supervision And Motivation On Employee Performance With Job Satisfaction As An Intervening Variable At The South Binjai Sub-District Office - Yodi Putama Sika; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2025)
Employee performance is influenced by various factors, including Supervision and Motivation provided by the organization. Effective supervision and proper motivation can increase Job Satisfaction, which further contributes to improved performance. This study aims to identify the influence of Supervision and Motivation on Employee Performance by considering the role of Job Satisfaction as an intervening variable in the South Binjai Sub-district Office. Data was obtained through a survey of employees with a quantitative approach and analyzed using the Partial Least Squares (PLS) method. The results of the analysis showed that Supervision and Motivation had a positive and significant influence on Job Satisfaction, with T-Statistic values of 4.718 and 4.838, respectively, and P-Value of 0.000. Job Satisfaction is proven to have a positive and significant influence on Employee Performance with a T-Statistic value of 9.799 and a P-Value of 0.000, emphasizing the importance of Job Satisfaction as a performance driving factor. Indirect influence analysis shows that Supervision and Motivation significantly affect Employee Performance through Job Satisfaction, with an influence coefficient of 0.384. These findings indicate that increased Supervision and Motivation will be more effective in encouraging Employee Performance when facilitated by high Job Satisfaction. Advice is provided to institutions to improve access to technology and training, as well as evaluate existing surveillance and motivation strategies. Researchers are further encouraged to explore other intervening variables, such as organizational culture and psychological capital, in the context of performance improvement.